A Multicenter Japanese Survey Assessing the Long-term Outcomes of Liver Retransplantation Using Living Donor Grafts. Issue 4 (April 2020) - Kuramitsu, Kaori; Fukumoto, Takumi; Egawa, Hiroto; Ohdan, Hideki; Umeshita, Koji; Uemoto, Shinji; Hibi, Taizo; Kasahara, Mureo; Yoshizumi, Tomoharu; Mizuta, Koichi; Shimamura, Tsuyoshi; Furukawa, Hiroyuki
Abstract : Background: Liver transplantation is the most suitable treatment option available for end-stage liver disease. However, some patients require retransplantation, despite medical advances that have led to improved survival. We aimed to compile a definitive, nationwide resource of liver retransplantation data in Japan, seeking to identify the predictors of patient survival posttransplantation. Methods: Questionnaires were sent to 32 institutions that had conducted 281 retransplantations before 2015. Results: Among the 265 patients included in this study (142 pediatric cases), the average age at primary transplantation was 23 years, and retransplantation was performed after an average of 1468 days. The main indication for retransplantation was graft rejection (95 patients). Living-donor liver transplantation accounted for 94.7% of primary transplantations and 73.2% of retransplantations. Patient survival at 1, 3, or 5 years did not differ by type of transplantation but was better for pediatric (70.8%, 68.3%, and 60.1%, respectively) than for adult (57.2%, 50.4%, and 45.2%, respectively) recipients ( P = 0.0003). Small-for-size syndrome, retransplantation within 365 days, and inpatient status at retransplantation were significant predictors of poor survival in pediatric cases. Retransplantation within 365 days and conditions warranting retransplantation were significant predictors of poor survival in adult patients. Conclusions: In Japan, where >70% of retransplantations are performed using living donors, the indications and timing are different from those in previous reports from other countries, while maintaining comparable survival rates. Considering technical challenges, graft failure within 365 days should be thoroughly restricted to justify the use of living donor.